Changes in vastus lateralis fibre cross‐sectional area, pennation angle and fascicle length do not predict changes in muscle cross‐sectional area. Issue 11 (30th September 2022) - Ruple, Bradley A.; Mesquita, Paulo. H. C.; Godwin, Joshua S.; Sexton, Casey L.; Osburn, Shelby C.; McIntosh, Mason C.; Kavazis, Andreas N.; Libardi, Cleiton A.; Young, Kaelin C.; Roberts, Michael D.
Abstract : New Findings: What is the central question of this study? Do changes in myofibre cross‐sectional area, pennation angle and fascicle length predict vastus lateralis whole‐muscle cross‐sectional area changes following resistance training? What is the main finding and its importance? Changes in vastus lateralis mean myofibre cross‐sectional area, fascicle length and pennation angle following a period of resistance training did not collectively predict changes in whole‐muscle cross‐sectional area. Despite the limited sample size in this study, these data reiterate that it remains difficult to generalize the morphological adaptations that predominantly drive tissue‐level vastus lateralis muscle hypertrophy. Abstract: Myofibre hypertrophy during resistance training (RT) poorly associates with tissue‐level surrogates of hypertrophy. However, it is underappreciated that, in pennate muscle, changes in myofibre cross‐sectional area (fCSA), fascicle length ( L f ) and pennation angle (PA) likely coordinate changes in whole‐muscle cross‐sectional area (mCSA). Therefore, we determined if changes in fCSA, PA and L f predicted vastus lateralis (VL) mCSA changes following RT. Thirteen untrained college‐aged males (23 ± 4 years old, 25.4 ± 5.2 kg/m 2 ) completed 7 weeks of full‐body RT (twice weekly). Right leg VL ultrasound images and biopsies were obtained prior to (PRE) and 72 h following (POST) the last training bout. Regression was used to assess if training‐induced changes in mean fCSA, PA and L f predicted VL mCSA changes. Correlations were also performed between PRE‐to‐POST changes in obtained variables. Mean fCSA (+18%), PA (+8%) and mCSA (+22%) increased following RT ( P < 0.05), but not L f (0.1%, P = 0.772). Changes in fCSA, L f and PA did not collectively predict changes in mCSA ( R 2 = 0.282, adjusted R 2 = 0.013, F 3, 8  = 1.050, P = 0.422). Moderate negative correlations existed for percentage changes in PA and L f ( r = −0.548, P = 0.052) and changes in fCSA and L f ( r = −0.649, P = 0.022), and all other associations were weak (| r | < 0.500). Although increases in mean fCSA, PA and VL mCSA were observed, inter‐individual responses for each variable and limitations for each technique make it difficult to generalize the morphological adaptations that predominantly drive tissue‐level VL muscle hypertrophy. However, the small subject pool is a significant limitation, and more research in this area is needed.